Gestational age affects the cerebellum development in neonatal infants: establishment of cerebellar extrauterine reference values as a function of gestational age - Rui-Ke Liu; Li Li; Xue-Qian Du; Ying Wang; Shuai Chen; Gui-Lian Li; Gui-Fang Li (Clinical and Experimental Obstetrics & Gynecology)
This study aims to provide the cerebellar extrauterine reference value related to gestational age by analysing the neonatal cerebellum development with different gestational age, by means of cranial ultrasound. A total of 376 eligible cranial ultrasound images of neonates with gestational age of 25 to 41 weeks were selected. Transverse cerebellar diameter, vermis height, vermis diameter, vermis circumference, vermis area and vermis eccentricity ratio were measured and followed by statistical analysis. Transverse cerebellar diameter formed a linear equation with the gestational age, which was Y = 0.104X + 0.176, R2 = 0.735 (P < 0.001). Vermis height formed a linear equation with the gestational age, which was Y = 0.069X - 0.328, R2 = 0.825 (P < 0.001). Vermis diameter formed a linear equation with the gestational age, which was Y = 0.051X - 0.604, R2 = 0.749 (P < 0.001). Vermis circumference formed a linear equation with the gestational age, which was Y = 0.284X - 1.709, R2 = 0.788 (P < 0.001). Vermis area formed a linear equation with the gestational age, which was Y = 0.227X - 4.445, R2 = 0.82 (P < 0.001). Vermis eccentricity ratio formed a linear equation with the gestational age, which was Y = -0.01X + 0.909, R2 = 0.142 (P < 0.001). The positive correlation between vermis height and gestational age was the strongest (r = 0.908, P < 0.001). The results provided that the cerebellar extrauterine reference range, between transverse cerebellar diameter, vermis height, vermis diameter, vermis circumference, vermis area, vermis eccentricity ratio of neonates of appropriate for gestational age. Gestational age is helpful for clinical diagnosis and evaluation of cerebellum growth and development of newborns.